Manejemen Sumber Daya Manusia Dalam Meningkatkan Kompetensi Bahasa Asing Peserta Didik Di Madrasah Diniyah Muallimin Pondok Zainul Hasanain Genggong Pajarakan Probolinggo - Rohmatul Hidayah; Nanang Qosim; Fuad Badruddin (Departement of Mathematics Education, 2024)
he focus of this research is how human resource management improves the foreign language competence of students at Madrasah Diniyah Muallimin Pondok Zainul Hasanain Genggong Pajarakan, and the implementation in realizing that students develop foreign language competence. Meanwhile, the aim is to describe the planning, implementation and evaluation process of human resource management in developing foreign language competency at the Zainul Hasanain Genggong Pajarakan Probolinggo Islamic boarding school. This research uses a qualitative approach, with descriptive methods. Data collection was carried out using observation, interview and documentation techniques. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Checking the validity of the findings was carried out by means of discussions with colleagues (co-workers) and triangulation techniques that used triangulation of sources and methods. The results of this research were that the process of planning, implementing and evaluating human resource management in foreign language development at the Zainul Hasanain Islamic boarding school, in carry it out through management functions, namely planning, implementing and evaluating human resource management in developing foreign languages at the Zainul Hasanain Genggong Pajarakan Islamic boarding school, Probolinggo.